Social issues faced by women when re-integrating into society following institutionalised rehabilitation for drug and alcohol addiction: from a social work perspective - Samaraweera, H. U. S. (National Science Foundation: Colombo, 2016)
The main aim of this paper is to analyse, from a social work perspective, the social issues faced by women when re-integrating into society following an institutionalised rehabilitation for drug and alcohol addiction.The research field is a drug and alcohol rehabilitation centre situated in the Colombo District. This paper provides an analytical description of seven female service users who were in the rehabilitation centre when the researcher was in the field because important information emerged from the female service users and as a means of narrowing the topic, even though this rehabilitation centre caters to both male and female drug and alcohol users. Dialogue and narrative methods were used to collect data and information based on a social work perspective. The main arguement in this paper is that drug and alcohol addiction is not merely an addiction of an individual based on his or her own motives, but rather, one that is intertwined with social factors. These female service users in the drug and alcohol rehabilitation centres should be understood in relation to the position ascribed to them in the process of social capital in terms of the low prestige, unemployment, economic insecurity, social stigma and social exclusion they experience. There is a need for a rehabilitation mechanism that operates with stability and transcends these negative societal factors.
Keywords: Social work; Drug and alcohol addiction; Social exclusion